Historia del arte e Imperio Azteca: la evidencia de las esculturas - Umberger, Emily (Revista Española de Antropología Americana, 2007)
Opinions on the nature of Aztec influence outside the Valley of Mexico vary greatly. They range from assertions of wide-spread material influences during the imperial period (1431-1521) to assertions of general cultural diffusions in central Mexico previous to the empire, and undermining its effects. A more nuanced understanding of the empire´s cultural influence lies somewhere between these two poles and requires the reconstruction of the particular histories of different areas. In the following essay the possible contributions of art history are explored through the analysis of sculptures from Aztec colony areas in the nearby Toluca Valley and in more distant North Veracruz.